BDNF Val66Met and reward-related brain function in adolescents: role for early alcohol consumption - Nees, Frauke; Dinu-Biringer, Ramona; Vollstädt-Klein, Sabine; Poustka, Luise; Banaschewski, Tobias; Mann, Karl; Rietschel, Marcella; Flor, Herta (Alcohol, 2015)
Changes in reward processing have been identified as one important pathogenetic mechanism in alcohol addiction. The nonsynonymous single nucleotide polymorphism in the brain-derived neurotrophic factor (BDNF) gene (rs6265/Val66Met) modulates the central nervous system activity of neurotransmitters involved in reward processing such as serotonin, dopamine, and glutamate. It was identified as crucial for alcohol consumption in healthy adults and, in rats, specifically related to the function in the striatum, a region that is commonly involved in reward processing. However, studies in humans on the association of BDNF Val66Met and reward-related brain functions and its role for alcohol consumption, a significant predictor of later alcohol addiction, are missing. Based on an intermediate phenotype approach, we assessed the early orientation toward alcohol and alcohol consumption in 530 healthy adolescents that underwent a monetary incentive delay task during functional magnetic resonance imaging. We found a significantly lower response in the putamen to reward anticipation in adolescent Met carriers with high versus low levels of alcohol consumption. During reward feedback, Met carriers with low putamen reactivity were significantly more likely to orient toward alcohol and to drink alcohol 2 years later. This study indicates a possible effect of BDNF Val66Met on alcohol addiction-related phenotypes in adolescence.